Accounting for the Heterogeneity in inter-generational links in educational attainment across Europe - Başlevent, C.; Kirmano?lu, H. (International Strategic Management Association, 2010)
We use data drawn from the European Social Survey to investigate the extent of inter-generational links in educational attainment across twenty-four European countries. We find that there is a lot of cross-country variation in the observed patterns especially when gender distinction is made at both the parents' and the children's generations. To account for the variation in the estimates obtained in separate country regressions, we propose the use of simple educational inequality measures as country-level control variables. While the variation in the children's educational attainment turns out to be positively associated with the level of inter-generational links, the opposite is the case for the variation in the parents' attainment. The introduction of country-level variables into the analysis brings about the estimation of the econometric models on the pooled sample of all countries and the use of multilevel modeling methods which we find to perform better than least squares estimation.
Keywords: Educational Attainment; European Social Survey; Hlm; Inter-Generational Links